IMPROVEMENT OF BUSINESS COMPETENCES AT THE UNIVERSITIES - Spīča, Inese; Spīčs, Ernests; Bērziņa, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Taking into consideration at the present business environment of the Republic of Latvia, as well as its geographical position and the historical backgroung, it is important to make use of these conditions for further improvement business competences at the universities of Latvia. The object of the present research paper is business competences, the subject of the research paper is analyses of the business competences on the higher education establishments in Latvia. The objective of the research paper is to study the integration process of students and academic staff representing Latvian higher education establishments in formation of business competences in Latvia, to elucidate the factors influencing the business competences, to develop proposals for improvement of business competences  in Latvia.. Research methods: reported analysis of business competences, higher educations establishments in Latvia, study of correlation between business environment factors and business competences, economic and statistical analysis of the universities results, economic experiment, study of public and non -governmental institutions data in Latvia. The present paper includes further development of study on the contents of business competences, factors influencing it, higher education theory and policy.